1994
DOI: 10.1161/01.hyp.24.6.663
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental influences on blood pressure in elderly twins.

Abstract: We used 289 pairs of Swedish twins reared apart or together to evaluate the importance of genetic and environmental influences on blood pressure. Unlike other twin and family studies, the adoption/twin design allows a distinction between estimates of the importance of shared rearing environments and genetic effects. Genetic factors were observed to play an important role for individual differences in blood pressure. Model-fitting analyses suggested upper limits of heritability for systolic and diastolic blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
69
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(74 citation statements)
references
References 31 publications
5
69
0
Order By: Relevance
“…In our study, covariance matrices for the two zygosity groups were subjected to structural-equation modeling with the LISREL 7 program (17) to estimate the genetic and environmental components of variance. The application of these techniques in the SATSA project has been described previously (18,19 gg/L). BPb was not influenced by smoking, and was slightly higher for men than for women (Table 1).…”
mentioning
confidence: 99%
“…In our study, covariance matrices for the two zygosity groups were subjected to structural-equation modeling with the LISREL 7 program (17) to estimate the genetic and environmental components of variance. The application of these techniques in the SATSA project has been described previously (18,19 gg/L). BPb was not influenced by smoking, and was slightly higher for men than for women (Table 1).…”
mentioning
confidence: 99%
“…Since 50-79% of the blood pressure variation in humans is thought to be due to genetic factors 6,7 we expect this percentage to be much higher in this and other similar populations. However shared environment in such intricate societies will be more difficult to address.…”
Section: And In Our Purelymentioning
confidence: 73%
“…4,5 Twins, family and adoptive studies have shown that at least 50-79% of the blood pressure variation in humans can be attributed to genetic factors. 6,7 Compared to the offspring of two normotensive parents, blood pressure is higher in the offspring of one normotensive and one hypertensive parent, and highest in the offspring of two hypertensive parents. 8 These distributions are evident in infancy and persists through late adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…4 Hypertension, a multifactorial disorder, results from the interaction of a complex set of environmental and genetic factors, which may vary with ethnicity, gender and geography. 5,6 It is essential to elucidate the prevalence and risk factors of hypertension, the most common atherosclerotic risk factor, for women to develop effective and efficient strategies for the prevention of CVD.…”
Section: Introductionmentioning
confidence: 99%